POTENSI PENGEMBANGAN PARIWISATA KABUPATEN DEMAK - Hartuti Purnaweni; Endang Susilowati (Universitas Diponegoro, 2020)
Demak is a religious tourism regency in the north coast of Central Java Province, well known as a City of Wali (Islamic Messenger) refer to its original position as center of the spread of Islamic teaching in Java. An overall effort for this initial position is mandatory. The aim of this research is to analyze: (1) The execution of tourism development in Demak Regency; (2) Factors related to the tourism development; (3) Efforts should be done by Demak regencial government in developing its tourism. Method employed is descriptive qualitative. Results of the research shows that tourism development in Demak has been related to the regencial management development. However, tourism development is still concentrated in the religious aspect, while Tourism Area Development zonation is not yet well applied. Internal factors hampers the development of tourism in Demak covering limited bus station infrastructure facilities, low coordination among tourism institutions, as well as lack of promotion and tourism service. However, there are supporting internal factors covers tourism attraction and accessibility. External factors hampers the development of tourism covering fund allocation from Central and Provincial government, professionalism of human resource, and low tourism awareness among local people. Meanwhile the supporting factors are the well kept cultural heritage, and the increasing number of tourist coming to this regency. Recommendation to the government is Demak regencial government should establish a special team to enhance tourism mindset among the local people, enhance professionalism of human resource in both the government and tourism managers (pengelola) through both qualitative and quantitative efforts in terms of various trainings and additional personnels.